2021
DOI: 10.1002/adfm.202010763
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Approach to Carbon‐Deficient and Oxygen‐Doped Graphitic Carbon Nitride: Robust Photocatalyst Against Recalcitrant Organic Pollutants and the Mechanism Insight

Abstract: Polymeric g‐C3N4 is a promising visible‐light‐responsive photocatalyst; however, the fast recombination of charge carriers and moderate oxidation ability remarkably restrict its photocatalytic oxidation efficiency towards organic pollutants. To overcome these drawbacks, a self‐modification strategy of one‐step formaldehyde‐assisted thermal polycondensation of molten urea to prepare carbon‐deficient and oxygen‐doped g‐C3N4 (VC‐OCN) is developed, and the carbon vacancy concentration is well‐controlled by changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(102 citation statements)
references
References 61 publications
4
87
0
Order By: Relevance
“…This finding indicated that few • OH radicals were generated in CN suspensions during photodegradation, which was probably resulted from the direct O 2 reduction through multi-electron reaction processes. [8,24] Unexpectedly, the [Mo 7 O 24 ] 6− -pCN sample exhibited an obviously enhanced characteristic signal with the intensity of 1:2:2:1, affirming that more • OH radicals were produced after intercalation, which could adsorb on catalyst surface for oxidation reactions. As presented in Figure 4c, only a weak characteristic signal from BMPO-• O 2 − adducts was detected over CN under Xe lamp irradiation (λ > 420 nm), whereas the signal was markedly enhanced in the [Mo 7 O 24 ] 6− -pCN system, and the peak intensities become stronger with the extension of the illumination time (Figure S14a O 24 ] 6− -pCN@BPA2, respectively), which were displayed in Figure 4e(i,ii).…”
Section: Mechanism Insights On Photocatalytic Oxidation Enhancementmentioning
confidence: 86%
See 2 more Smart Citations
“…This finding indicated that few • OH radicals were generated in CN suspensions during photodegradation, which was probably resulted from the direct O 2 reduction through multi-electron reaction processes. [8,24] Unexpectedly, the [Mo 7 O 24 ] 6− -pCN sample exhibited an obviously enhanced characteristic signal with the intensity of 1:2:2:1, affirming that more • OH radicals were produced after intercalation, which could adsorb on catalyst surface for oxidation reactions. As presented in Figure 4c, only a weak characteristic signal from BMPO-• O 2 − adducts was detected over CN under Xe lamp irradiation (λ > 420 nm), whereas the signal was markedly enhanced in the [Mo 7 O 24 ] 6− -pCN system, and the peak intensities become stronger with the extension of the illumination time (Figure S14a O 24 ] 6− -pCN@BPA2, respectively), which were displayed in Figure 4e(i,ii).…”
Section: Mechanism Insights On Photocatalytic Oxidation Enhancementmentioning
confidence: 86%
“…After being excited, CN showed two decay times ≈1.81 and 9.40 ns, which originated from the spontaneous radiation decay and nonradiative transition of charge carriers, respectively. [24] After intercalation, the average PL lifetime (Ave. τ) was prolonged from 7.53 ns (CN) to 8.82 ns ([Mo 7 O 24 ] 6− -pCN), stating that the sandwiched Mo-POMs could gather photoelectrons from planar aromatic rings and thus severely hindered the recombination of e − -h + pairs. [29] Electron paramagnetic resonance (EPR) examination was also conducted to verify the unique electronic structure and unpaired electrons of different catalysts (Figure S10, Supporting Information).…”
Section: Characterizations Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, some additional e − and h + are generated in the VB and CB of GDY. Since carbon vacancies at the CuS@GDY interfaces are active centers for adsorption and decomposition of H 2 O 2 , [28] plentifully localized e − and h + can react with H 2 O 2 molecules to produce a large amount of O 2 (Equation 1) and •OH radicals (Equation 2), and further convert to •O 2 − anion radicals via oneelectron oxygen reduction (Equation 3). Meanwhile, •O 2 − anion radicals combine with h + to yield 1 O 2 (Equation 4).…”
Section: Kinetics and Mechanism Of Cus@gdy As A Photocatalytic Enzyme...mentioning
confidence: 99%
“…The interaction of PVDF-HFP and PCN causes the valence band to further move towards the fermi level. [46] The narrowed energy gap make the electrons more easily activated by external electrical field, beneficial to the piezoelectric catalysis. Correspondingly, the differential charge density diagram in Figure 6d shows that the presence of PVDF will lead to electron accumulation on the surface of PCN, which is conducive to the piezocatalytic reaction process.…”
Section: Resultsmentioning
confidence: 99%